2023
DOI: 10.3390/molecules28010407
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Bioengineering with Fibrin Scaffolds and Deproteinized Bone Matrix Associated or Not with the Transoperative Laser Photobiomodulation Protocol

Abstract: Extending the range of use of the heterologous fibrin biopolymer, this pre-clinical study showed a new proportionality of its components directed to the formation of scaffold with a lower density of the resulting mesh to facilitate the infiltration of bone cells, and combined with therapy by laser photobiomodulation, in order to accelerate the repair process and decrease the morphofunctional recovery time. Thus, a transoperative protocol of laser photobiomodulation (L) was evaluated in critical bone defects fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…We can highlight properties such as the reduction of pain, inflammation and edema, assisting in the healing process and accelerating the tissue repair process [76,77]. Regarding this last property, studies have already demonstrated that LLLT is already widely used in the area of rehabilitation and regenerative medicine to accelerate the regeneration of different types of tissue in the human body, such as nervous tissue [78][79][80][81]; muscles [82]; bone tissue [83][84][85][86]; respiratory tract tissue [87]; tissues affected by burns [88] and other body tissue types [89]. Metin et al (2018) obtained positive results when using LLLT in soft and hard tissues after endodontic surgery, such that the laser group presented better results in relation to tissue repair, increase in bone volume and density and decrease in postoperative pain [90].…”
Section: Discussionmentioning
confidence: 99%
“…We can highlight properties such as the reduction of pain, inflammation and edema, assisting in the healing process and accelerating the tissue repair process [76,77]. Regarding this last property, studies have already demonstrated that LLLT is already widely used in the area of rehabilitation and regenerative medicine to accelerate the regeneration of different types of tissue in the human body, such as nervous tissue [78][79][80][81]; muscles [82]; bone tissue [83][84][85][86]; respiratory tract tissue [87]; tissues affected by burns [88] and other body tissue types [89]. Metin et al (2018) obtained positive results when using LLLT in soft and hard tissues after endodontic surgery, such that the laser group presented better results in relation to tissue repair, increase in bone volume and density and decrease in postoperative pain [90].…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of the heterologous fibrin biopolymer, its formula and forms of application are in accordance with patent number BR102014011432-7, issued on 6 July 2022, by the National Institute of The number of animals per group (n = 10) was based on previous studies with the necessary quantity to favor statistical data, maintaining the policy of reducing the use of animals in research. Euthanasia periods of 14 and 42 days were also used in previous studies, with 14 days being used to evaluate PBM in the initial stages of inflammation and 42 days for the possible increase in the percentage of bone formed [23,59,60].…”
Section: Experimental Surgerymentioning
confidence: 99%
“…HFB is composed of three fractions that are homogenized and applied in sequence, at the lesion site in a total volume of 6 µL: (I) fibrinogen cryoprecipitate derived from the blood of Bubalus bubalis (3 µL), (II) calcium chloride diluent (2 µL), and (III) gyroxin, a thrombin-like enzyme from the Crotalus durissus terrificus snake (1 µL) [35][36][37]. The third fraction added is responsible for the polymerization process, allowing the coaptation and stabilization of the roots, which can be observed during the surgical process [38][39][40]. HFB components and application formulas are listed in its patent (BR1020140114327) and were kindly provided by the Center for the Study of Venoms and Venomous Animals (CEVAP/UNESP, Brazil).…”
Section: Root Replantation and Hfbmentioning
confidence: 99%